2017
DOI: 10.1186/s12864-017-3769-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of innate immunity reveals novel and conserved components in crustacean food crop species

Abstract: BackgroundGrowing global demands for crustacean food crop species have driven large investments in aquaculture research worldwide. However, large-scale production is susceptible to pathogen-mediated destruction particularly in developing economies. Thus, a thorough understanding of the immune system components of food crop species is imperative for research to combat pathogens.ResultsThrough a comparative genomics approach utilising extant data from 55 species, we describe the innate immune system of the class… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 251 publications
(227 reference statements)
5
49
0
Order By: Relevance
“…This assumption, which was already suggested by Christiaens et al (2015) and Taning et al (2016a) is also supported by reports of Loquacious being functional as cofactor to Dicer-2 in the siRNA pathway in D. melanogaster (Czech et al, 2008;Marques et al, 2010;Okamura et al, 2008). In Crustacea, another protein has been identified as a cofactor for Dicer-2, namely an orthologue of the transactivating response (TAR) RNA binding protein (TRBP) (Lai and Aboobaker, 2017).…”
Section: Rnai Machinery Genes Repertoiresupporting
confidence: 55%
“…This assumption, which was already suggested by Christiaens et al (2015) and Taning et al (2016a) is also supported by reports of Loquacious being functional as cofactor to Dicer-2 in the siRNA pathway in D. melanogaster (Czech et al, 2008;Marques et al, 2010;Okamura et al, 2008). In Crustacea, another protein has been identified as a cofactor for Dicer-2, namely an orthologue of the transactivating response (TAR) RNA binding protein (TRBP) (Lai and Aboobaker, 2017).…”
Section: Rnai Machinery Genes Repertoiresupporting
confidence: 55%
“…Sequence analysis of terrestrial isopod ALFs indicated that they have two conserved cysteine residues suggestive of disulfite bridge formation [27] (Supplementary File S1), as previously described for other malacostracan ALFs [27]. The region located between these cysteine residues is considered as a LPS-binding domain formed with positively charged amino acids [27]. As this domain is also present in other malacostracan ALFs [27], it suggests LPS-binding conservation across the whole gene family.…”
Section: Description Of the Alf And Crustin Repertoire Of Terrestrialsupporting
confidence: 53%
“…The highest number of ALFs (15 transcripts) was identified in Trachelipus rathkei (Figure 1 and Supplementary Table S2). Sequence analysis of terrestrial isopod ALFs indicated that they have two conserved cysteine residues suggestive of disulfite bridge formation [27] (Supplementary File S1), as previously described for other malacostracan ALFs [27]. The region located between these cysteine residues is considered as a LPS-binding domain formed with positively charged amino acids [27].…”
Section: Description Of the Alf And Crustin Repertoire Of Terrestrialmentioning
confidence: 70%
See 2 more Smart Citations